Female acts in Greek tragedy - Foley, Helene P., 1942- (Princeton, N.J. : Princeton University Press, 2001)
Although Classical Athenian ideology did not permit women to exercise legal, economic, and social autonomy, the tragedies of Aeschylus, Sophocles, and Euripides often represent them as influential social and moral forces in their own right. Scholars have struggled to explain this seeming contradiction. Helene Foley shows how Greek tragedy uses gender relations to explore specific issues in the development of the social, political, and intellectual life in the polis. She investigates three central and problematic areas in which tragic heroines act independently of men: death ritual and lamentat.
The politics of tragic lamentation -- The contradictions of tragic marriage -- Women as moral agents in Greek tragedy -- Virgins, wives, and mothers; Penelope as paradigm -- Sacrificial virgins: Antigone as moral agent -- Tragic wives: Clytemnestras -- Tragic wives: Medea's divided self -- Tragic mothers: maternal persuasion in Euripides -- Anodos dramas: Euripides' Alcestis and Helen.
Includes bibliographical references (pages 339-368) and index.
Print version record.
English.
JSTOR
Keywords: Greek drama (Tragedy) -- History and criticism; Women and literature -- Greece; Women in literature; Tragédie grecque -- Histoire et critique; Femmes et littérature -- Grèce.; Femmes dans la littérature.; DRAMA -- Ancient, Classical & Medieval; Greek drama (Tragedy); Women and literature; Women in literature; Greece; Criticism, interpretation, etc